2016
DOI: 10.1007/s00213-016-4455-y
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic assessment of demand for cigarettes, snus, and nicotine gum

Abstract: Rationale Behavioral economic measures of demand provide estimates of tobacco product abuse liability and may predict effects of policy-related price regulation on consumption of existing and emerging tobacco products. Objective In the present study, we examined demand for snus, a smokeless tobacco product, in comparison to both cigarettes and medicinal nicotine. We used both a naturalistic method in which participants purchased these products for use outside the laboratory, as well as laboratory-based self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The following alternative products were available to participants in the units and at the prices (determined by local average price or in the case of internet purchases for electronic cigarette components, account balance was based on the internet price) indicated: their usual brand of cigarettes (packs, 19.6 mg of nicotine), winterchill flavor Camel Snus® (15-pouch tins, $2.89 each, R.J. Reynolds, Winston-Salem, NC, U.S.A., 27.75 mg of nicotine), classic flavor Skoal dip® (16.8-oz tins, $4.54 each, US Smokeless Tobacco Company, Richmond, VA, U.S.A., 62.4 mg of nicotine), white ice mint flavor Nicorette 4-mg nicotine gum® (20-count packages, $16 each, McNeil Consumer Healthcare, Fort Washington, PA, U.S.A., 80 mg of nicotine), and mint flavor Nicorette 4-mg nicotine lozenges® (20-count packages, $12 each, McNeil Consumer Healthcare, Fort Washington, PA, U.S.A., 80 mg of nicotine). These products were chosen based on availability at local retail outlets and prior research from our laboratory (Stein et al, 2016) indicating specific brands and flavors were tolerable. Each of four price conditions ($0.12, $0.25, $0.50, and $1.00 per cigarette) were presented in a random order to all participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following alternative products were available to participants in the units and at the prices (determined by local average price or in the case of internet purchases for electronic cigarette components, account balance was based on the internet price) indicated: their usual brand of cigarettes (packs, 19.6 mg of nicotine), winterchill flavor Camel Snus® (15-pouch tins, $2.89 each, R.J. Reynolds, Winston-Salem, NC, U.S.A., 27.75 mg of nicotine), classic flavor Skoal dip® (16.8-oz tins, $4.54 each, US Smokeless Tobacco Company, Richmond, VA, U.S.A., 62.4 mg of nicotine), white ice mint flavor Nicorette 4-mg nicotine gum® (20-count packages, $16 each, McNeil Consumer Healthcare, Fort Washington, PA, U.S.A., 80 mg of nicotine), and mint flavor Nicorette 4-mg nicotine lozenges® (20-count packages, $12 each, McNeil Consumer Healthcare, Fort Washington, PA, U.S.A., 80 mg of nicotine). These products were chosen based on availability at local retail outlets and prior research from our laboratory (Stein et al, 2016) indicating specific brands and flavors were tolerable. Each of four price conditions ($0.12, $0.25, $0.50, and $1.00 per cigarette) were presented in a random order to all participants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, evaluation of the reinforcing efficacy (i.e., the relative ability to maintain or change behavior) of Snus in a self-administration paradigm concluded that Snus administration was associated with decreased latency to smoke cigarettes in males, but not females (Barrett et al, 2011). Similarly, in a naturalistic demand assessment study, males were more likely to purchase Snus than females(Bickel et al, in press; Stein et al, 2016). …”
Section: Introductionmentioning
confidence: 92%
“…Essential value cannot be computed for participants with null demand, however, we coded essential value as zero (ie, lowest potential value) in these cases because it is plausible that participants did not find the alternative products appealing and exclusion would overestimate alternative product demand. 35 Essential value, 36 1/(100 × α × k 1.5 ), was computed for those with systematic purchase task data, and estimates were square root transformed to improve distributions. Elasticity For this equation, Q = consumption at a given cost, Q 0 = consumption when cost is zero, C = cost, and k = a constant that denotes the range of consumption in log powers of 10.…”
Section: Data Analysesmentioning
confidence: 99%
“…To date, two studies have used the purchase task methodology to address abuse liability, at least to an extent. Stein et al ( 2017) examined demand for snus (an oral tobacco product), typical combustible tobacco cigarettes, and nicotine replacement gum, finding that elasticity for snus was significantly higher than cigarettes (but not gum) and intensity of demand for gum was significantly lower than both snus and cigarettes. Thus, the purchase task revealed differing reinforcing value by nicotine delivery formulation.…”
Section: Introductionmentioning
confidence: 99%